ESG PERFORMANCE AND RISK-RETURN CORRESPONDENCE FOR THE LARGE ENERGY COMPANIES DURING THE COVID-19 PANDEMIC - KAMINSKYI, Andrii; SHALENYK, Ivan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This paper investigates the relationship between Environmental, Social, and Governance (ESG) performance and the risk-return characteristics of publicly traded energy companies from 2019 to 2023. Using a sample of 39 companies across different energy subsectors, including oil & gas, utilities, and renewable energy, this study offers a two-part analysis. First, correlation analysis shows no statistically significant linear relationships between aggregate ESG scores and both annual returns and risk. These results are consistent with previous empirical findings that highlight the long-term nature of ESG signals. Second, K-means cluster analysis reveals three distinct company profiles based on ESG, return, and volatility, thereby uncovering hidden patterns that traditional regression models often fail to capture. The clusters include: (1) high-return/high-risk extractive companies with low ESG scores; (2) infrastructure firms with moderate ESG ratings and variable performance; and (3) ESG leaders, mainly in renewable energy, with low risk and moderate returns. The results indicate that ESG may not serve as a short-term predictor of stock performance but rather as an indicator of strategic resilience. This paper contributes to ESG literature by proposing clustering as a viable approach for creating typologies in sector-specific ESG research. Limitations and future research directions are discussed, highlighting the need to develop dynamic, nonlinear models, apply machine learning techniques, and conduct sensitivity analyses under various economic conditions.
Keywords: ESG performance; energy sector; stock returns; risk; cluster analysis; sustainable finance; finance performance